2008
DOI: 10.1007/s10778-008-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

Limit equilibrium of an orthotropic plate weakened by a periodic row of collinear cracks

Abstract: A modified d c -model is used to study the limiting state of an orthotropic plate weakened by a periodic row of collinear cracks and satisfying a general failure criterion. The failure mechanism of the plate is analyzed. A study is made of the effects of the degree of orthotropy, the biaxiality of external loading, and the geometrical parameters on the fracture process zones at the crack tips and the limiting state of the plate. The safe loading of an orthotropic viscoelastic plate with a periodic row of colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The design of a compound plate weakened by a periodic set of cracks was considered in [4]. Orthotropic plates weakened by a periodic number of collinear cracks were addressed in [7]. The exact solution (as a function of four constants of integration) for and an equation for the critical compressive load of a column with an arbitrary number and arrangement of cracks were obtained in [8].…”
mentioning
confidence: 99%
“…The design of a compound plate weakened by a periodic set of cracks was considered in [4]. Orthotropic plates weakened by a periodic number of collinear cracks were addressed in [7]. The exact solution (as a function of four constants of integration) for and an equation for the critical compressive load of a column with an arbitrary number and arrangement of cracks were obtained in [8].…”
mentioning
confidence: 99%
“…An extensive review of relevant studies can be found in [3]. The limit state of an orthotropic plate with periodic cracks is analyzed in [12,13]. The stress-strain state of spherical shells with an eccentric circular hole and prestressed shells was studied in [14,18].…”
mentioning
confidence: 99%